OP0056 Macitentan in Patients with Digital Ulcers Associated with Systemic Sclerosis: Results from the Dual-1 and Dual-2 Randomised Controlled Trials. (9th June 2015) - Denton, C.P.; Khanna, D.; Krieg, T.; Le Brun, F.-O.; Merkel, P.A.; Papadakis, K.; Pope, J.; Matucci Cerinic, M.; Furst, D.E.
Abstract : Background: Digital ulcers (DUs) are a manifestation of the underlying vasculopathy in systemic sclerosis. They can cause serious complications, including infection and digital loss, and impact hand function and quality of life. Bosentan, an endothelin receptor antagonist, has previously been shown to reduce the occurrence of new DUs in systemic sclerosis. Objectives: We report results of two randomised placebo-controlled trials (DUAL-1 and DUAL-2), designed to assess the potential benefit of the endothelin receptor antagonist macitentan on DUs in patients with systemic sclerosis and ongoing DU disease. Methods: DUAL-1 and DUAL-2 were independent, multicenter, randomized, placebo-controlled, double-blind, parallel group trials that assessed the efficacy, safety, and tolerability of macitentan on DUs in patients with systemic sclerosis and at least 1 active DU. The target enrolment for each trial was 285 patients. Patients were randomised (1:1:1) to placebo, macitentan 3 mg or macitentan 10 mg once daily and were stratified according to the number of DUs at baseline (≤3 or >3). The primary outcome measure was the reduction of the cumulative number of new DUs at 16 weeks of treatment. Secondary assessments included hand functionality and DU burden. Safety and tolerability were also assessed. In each trial, the primary analysis was performed on all randomised patients. Results: In DUAL-1, 289 patients were randomized to placebo (n=97), macitentan 3 mg (n=95), and macitentan 10 mg (n=97). In DUAL-2, 265 patients were randomized to placebo (n=89), macitentan 3 mg (n=88), and macitentan 10 mg (n=88). DUAL-2 was prematurely terminated based on the recommendation of the Independent Data Monitoring Committee, who determined that additional data were unlikely to result in a positive primary outcome measure; no unexpected safety findings were observed. The primary endpoint was not met in either trial (Table ). There were no significant differences between active treatment and placebo for any of the secondary endpoints. In DUAL-1, 67.0%, 64.1%, and 63.0% of patients treated with placebo, macitentan 3 mg and macitentan 10 mg respectively had no new DUs by week 16, and 59.8%, 56.0%, and 54.8% of patients respectively in DUAL-2. Macitentan was well tolerated; adverse events (incidence >10%) that occurred more frequently with macitentan versus placebo (≥3% placebo-corrected difference) in DUAL-1 were headache and peripheral oedema, and in DUAL-2 were peripheral oedema, anaemia, nasopharyngitis, upper respiratory tract infection, skin ulcer, and diarrhoea. Conclusions: In the DUAL-1 and DUAL-2 studies, treatment with macitentan did not reduce the cumulative number of new DUs over 16 weeks in patients with systemic sclerosis. These results do not support the use of macitentan for the treatment of DUs in this patient population. Acknowledgements: The DUAL trials were funded by Actelion Pharmaceutical Ltd. The authors express their gratitude to all investigators and patients who participated in these trials. Disclosure of Interest: C. Denton Grant/research support from: Actelion, Novartis and CSL Behring, Consultant for: Roche, Actelion, GSK, Inventiva and Boehringer Ingelheim, D. Khanna Grant/research support from: Actelion, Bayer, Biogen Idec, Bristol-Myers Squibb, EMD Serono, Gilead, InterMune, NIH, PH Association and the Scleroderma Foundation, Consultant for: Actelion, Bayer, Biogen Idec, Bristol-Myers Squibb, Cytori, EMD Serono, Genentech/Roche, GlaxoSmithKline, InterMune, Lycera, Sanofi-Aventis/Genzyme, T. Krieg Grant/research support from: Actelion, Consultant for: Actelion, F.-O. Le Brun Shareholder of: Actelion, Employee of: Actelion, P. Merkel Grant/research support from: Actelion, Bristol-Myers Squibb, Celgene, ChemoCentryx, Genentech/Roche and GlasoSmithKline, Consultant for: Actelion, Alexion, ChemoCentryx and Sanofi-Aventis/Genzyme, K. Papadakis Shareholder of: Actelion, Employee of: Actelion, J. Pope Grant/research support from: Actelion, Consultant for: Actelion, M. Matucci Cerinic Grant/research support from: Actelion, Speakers bureau: Actelion, GlasoSmithKline, Pfizer, AbbVie, MSD, Hospira and Bristol-Myers Squibb, D. Furst Grant/research support from: AbbVie, Actelion, Amgen, Bristol-Myers Squibb, Gilead, GlaxoSmithKlein, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, Bristol-Myers Squibb, Cytori, Janssen, Gilead, GlaxoSmithKlein, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: AbbVie, Actelion, UCB